Survei Kepuasan Pelanggan Berbasis Dekstop (Penelitian Terhadap PT.Gowa Modern Motor) - Mega Khaerunisah; Sutan Moh Arif; Nur Ali (CV. Multi Kreasi Media, 2024)
PT. Gowa Modern Motor or what we usually know is Hyundai was founded in 2020. Hyundai Motor Company, is an automotive company that is a division of Hyundai Motor Group and is the largest car manufacturer in South Korea. PT. Gowa Modern Motor or Hyundai has a vision and mission, namely